Produktivitas Itik Mojosari Umur 24 Minggu dengan Pemberian Suplementasi Tepung Ikan Rucah : Productivity of Mojosari Ducks Aged 24 Weeks by Providing Rucah Fish Meal Supplementation - Rinawidiastuti, Rinawidiastuti; Budiarto, Alip (Jurnal Riset Agribisnis dan Peternakan, 2022)
Trash fish is fish with high protein content and low price. This research aims to determine the level of trash fish meal supplementation on the productivity of laying ducks. This experiment used 60 Mojosari ducks in 24 weeks. The feed treatment given to ducks is as follows; P0, P1, P2 and P3 each containing 0; 2.5; 5 and 7.5% TIR. The method used in this research is an experimental method with a Completely Randomized Design (CRD) consisting of 4 treatments and 5 replications. The parameters observed were feed nutritional content, PK consumption, PK consumption, drinking consumption, and PBBH. The results showed that trash fish meal had a significant effect (P<0.05) on BK consumption of 123.85; 127.05; 130.19 and 131.93 grams. PK consumption had a significant effect (P<0.05) with a percentage of 14.29; 14.54; 14.79 and 15.04%. Drinking water consumption had no significant effect (P>0.05) with a number of 912.23 911; 898 and 911.33 ml. PBBH had no significant effect (P>0.05) at 0.79; 0.93; 0.91 and 0.87 grams. The conclusion was that trash fish meal had an effect on BK and PK consumption, but had no effect on drinking water consumption and PBBH.